First Insights Into the Growth and Population Structure of Cottoperca trigloides (Perciformes, Bovichtidae) From the Southwestern Atlantic Ocean - Lattuca, María Eugenia; Llompart, Facundo; Avigliano, Esteban; Renzi, Marta; De Leva, Ileana; Boy, Claudia Clementina; Vanella, Fabián Alberto; Barrantes, María Eugenia; Fernández, Daniel Alfredo; de Albuquerque, Cristiano Queiroz (Frontiers in Marine Science, 2020)
The aim of this work was to describe the growth of Cottoperca trigloides, a notothenioid species with a non-Antarctic distribution, and to test the existence of different nursery areas and fish stocks through changes in the otolith elemental composition. Fish were collected during spring 2009 over the Patagonia continental shelf, including the Marine Protected Area Namuncurá/Burdwood Bank, in the southwestern Atlantic Ocean. The age and growth analysis were performed by counting marks in sagittae, assuming an annual periodicity of their deposition, and identified 8-year classes (0+ to 7+). Given the size range of the fish, length-at-age data were fitted to the Gompertz growth model TLt = 55.45 [exp ((exp) -0.32 (t – 1.89))], explaining more than 95% of the growth pattern. Moreover, the chemical composition of otolith core and edge areas was analyzed by laser ablation inductively coupled plasma mass spectrometry. The canonical analysis of principal coordinates successfully allocated 72.92% of the fish for the core and 91.67% for the edge area of the otolith, in three groups corresponding to ‘northern Patagonia shelf’, ‘southern Patagonia shelf’ and ‘Marine Protected Area Namuncurá/Burdwood Bank’ areas, suggesting a high segregation among them over the Patagonian shelf. Thus, otolith elemental composition has proven to be an efficient approach to identify different nursery areas and stocks for the species. Present results provide new information on the growth and the population structure of C. trigloides, from a geographical area where information on this issue is still scarce, constituting an essential tool to develop conservation principles for the species.